MyD88-dependent signaling drives toll-like receptor-induced trained immunity in macrophages - Owen, Allison M.; Luan, Liming; Burelbach, Katherine R.; McBride, Margaret A.; Stothers, Cody L.; Boykin, Olivia A.; Sivanesam, Kalkena; Schaedel, Jessica F.; Patil, Tazeen K.; Wang, Jingbin; Hernandez, Antonio; Patil, Naeem K.; et al. (Frontiers in Immunology, 2022)
Immunocompromised populations are highly vulnerable to developing life-threatening infections. Strategies to protect patients with weak immune responses are urgently needed. Employing trained immunity, whereby innate leukocytes undergo reprogramming upon exposure to a microbial product and respond more robustly to subsequent infection, is a promising approach. Previously, we demonstrated that the TLR4 agonist monophosphoryl lipid A (MPLA) induces trained immunity and confers broad resistance to infection. TLR4 signals through both MyD88- and TRIF-dependent cascades, but the relative contribution of each pathway to induction of trained immunity is unknown. Here, we show that MPLA-induced resistance to Staphylococcus aureus infection is lost in MyD88-KO, but not TRIF-KO, mice. The MyD88-activating agonist CpG (TLR9 agonist), but not TRIF-activating Poly I:C (TLR3 agonist), protects against infection in a macrophage-dependent manner. MPLA- and CpG-induced augmentation of macrophage metabolism and antimicrobial functions is blunted in MyD88-, but not TRIF-KO, macrophages. Augmentation of antimicrobial functions occurs in parallel to metabolic reprogramming and is dependent, in part, on mTOR activation. Splenic macrophages from CpG-treated mice confirmed that TLR/MyD88-induced reprogramming occurs in vivo. TLR/MyD88-triggered metabolic and functional reprogramming was reproduced in human monocyte-derived macrophages. These data show that MyD88-dependent signaling is critical in TLR-mediated trained immunity.